Advancing the science behind animal program sustainability: An overview of the special issue. Issue 1 (10th January 2019) - Powell, David M.; Dorsey, Candice L.; Faust, Lisa J.
Abstract : Over the last ten years, zoos and aquariums around the world have been coming to grips with the "sustainability crisis" – the realization that most of our collaboratively managed animal populations are not viable for the long‐term. Many initiatives have been launched at the regional, zoological association, program, and institutional levels to improve the long‐term trajectories of these populations. This Special Issue of Zoo Biology highlights some of the scientific approaches that are aimed at addressing population viability and sustainability challenges. The approaches range from development of new analytical tools, to analysis of large datasets, and re‐examination of population management principles and philosophies. While much progress has been made in the last ten years, it is clear that continued work on population viability and sustainability is critical and difficult management decisions must be made. In this paper, we identify some of the actions that the zoological community can take to fortify our animal programs and prevent the outright extinction of species.